Lithiumnachweis bei exhumierten Leichen: Vergleichende Untersuchungen von Knochensubstanz und Erdreich bei V. a. todesursächliche Lithiumintoxikation - Stöver, A.; Roider, G.; Schwarze, Bernd; Staudt, Svenja; Graw, M.; Schöpfer, J. (Rechtsmedizin, 2019)
Background: Lithium salts have been used in psychiatric therapy for decades. The endogenous lithium content of organs and body fluids is just as heterogeneous as the content due to medication. There are no comparative data in the literature on endogenous or medication-related lithium contents and distribution in a corpse in cases of advanced putrefaction. Data on the possible transfer of lithium from or into surrounding soil also do not exist. In view of the lack of sufficient data in the literature on post-mortem lithium concentrations in bone with or without lithium medication, it seemed reasonable to carry out investigations. Material and method: The study included samples from a total of five adult corpses plus soil samples from the area where the bodies were found. After exact weighing and appropriate sample preparation with a graphite furnace AAS (graphite furnace atomic absorption spectroscopy, spectrometer ZEEnit650 graphite furnace, Analytik Jena) the sample material (bone, bone marrow, soil) was measured against an aqueous calibration by the method of standard addition and, if necessary in lower concentration ranges. Results: The lithium concentrations detected in the skeletal samples from cases I, II and III (no references about lithium therapy) were 70–130 μg/kg wet weight for bone and 10–20 μg/kg wet weight for bone marrow. They differed by a factor of ca. 200 compared to the concentration in lithium-based medication for bones and by a factor of ca. 400 for bone marrow. Furthermore, it was shown that all bone marrow concentrations were significantly lower compared to the concentrations in bone. The measured lithium content of all soil samples examined in the collective was 10–30 mg/kg of soil and in a comparatively middle range worldwide. Conclusion: Because of the lack of comparative values in the literature, lithium concentrations in bone, bone marrow and soil samples of exhumed or buried corpses were examined and compared to results in corpses with lithium therapy before death. The lithium concentrations found in the bone substance of lithium-medicated and non-medicated corpses showed highly statistically significant differences of 2–4 × 102. A measurement of the lithium concentrations in corpses in a state of advanced putrefaction or skeletonized corpses, in bone marrow and/or only bone seems to be a useful to identify cases of lithium medication or poisoning; however, based on current data a distinction between therapeutic use and poisoning is not yet sufficiently possible.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Atomic absorption spectroscopy; Bone; Exhumation; Lithium; Poisoning